Діагностика та добір операції за вузлового еутиреоїдного зоба - Гіленко, І. О.; Дем’янюк, Д. Г.; Ляховський, В. І.; Крижановський, О. А.; Горлачов, М. І.; Сакевич, П. П.; Дудченко, М. О.; Шкурупій, О. А.; Діхтенко, Т. Г. (Clinical Endocrinology and Endocrine Surgery, 2008)
562 patients with the nodular euthyroid goiter were observed during 10 years. Female — 541(96,3%), Male — 21(3,7%). The age of the patients 23-72 years. During the observation the thyrtrophic hormone, thyroxin, triiodothyronine concentration tests were performed. Ultrasonic diagnostics and MRI were performed under indications. All the patients passed the fine-needle node biopsy. The final morphological diagnostics was performed on the operating table using the method of the express-biopsy. The colloid goiter was diagnosed at 354(62,9%) cases, the combination of adenoma and colloid goiter was diagnosed at 168(29,8%) cases, the cancer was diagnosed at 24(4,2%) cases. Subtotal resection of one gland lobe was executed at 9 (1,6%) cases, hemithyroidectomy was executed at 395(73,4%) cases, hemithyroidectomy and subtotal resection of opposite gland lobe was executed at 129(23,9%) cases, thyreoidectomy was performed at 5(0,9%) cases. In case of malignant processes the whole gland was removed. All the patients have recovered.